2010
DOI: 10.1159/000302712
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Lipid Metabolism in Chronic Nephropathies: Mechanisms, Diagnosis and Treatment

Abstract: Nephropathic subjects show an increased tendency to develop cardiovascular diseases, mainly as the consequence of several risk factors including increased oxidative stress, inflammation, physical inactivity, anemia, vascular calcification, and endothelial dysfunction. The alterations in lipid metabolism represent a relatively lesser important cause of genesis and progression of atherosclerosis. Unfortunately, in these patients the atherogenic potential of dyslipidemia may depend more on apolipoproteins than on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 148 publications
2
31
0
4
Order By: Relevance
“…Standards (0.1-10 g/ml), made up in methanol and extracts redissolved in 100 l methanol, were analyzed in triplicate by injection of 20 l. The intraday cross-validation (CV; n = 3) at a concentration of 2.5 g/ml was the general population and is dependent on the stage of disease ( 9,10 ). In some patients, total cholesterol and LDL-cholesterol are not elevated, while patients on hemodialysis may even have reduced cholesterol compared with control subjects ( 11 ). It is apparent that CKD involves multiple lipid abnormalities, some of which may contribute to increased CVD risk.…”
Section: Vitamin E Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Standards (0.1-10 g/ml), made up in methanol and extracts redissolved in 100 l methanol, were analyzed in triplicate by injection of 20 l. The intraday cross-validation (CV; n = 3) at a concentration of 2.5 g/ml was the general population and is dependent on the stage of disease ( 9,10 ). In some patients, total cholesterol and LDL-cholesterol are not elevated, while patients on hemodialysis may even have reduced cholesterol compared with control subjects ( 11 ). It is apparent that CKD involves multiple lipid abnormalities, some of which may contribute to increased CVD risk.…”
Section: Vitamin E Contentmentioning
confidence: 99%
“…Plots are total lipids detected (A), TAGs (B), total PC (C), ratio of pPE to total PE (D), total LPC and LPE (E), and ratio of LPC to LPE (F). classes ( 7,11,39 ). To test the hypothesis that molecular information about LDL lipidomic profi le would reveal novel details of dyslipidemia in CKD, we used a top-down lipidomic approach that allows a comparative analysis ( 20,22,23 ) of the LDL lipid profi le from age-matched controls and patients with stage 4/5 CKD.…”
Section: Statistical Analysis Discriminated Control and Ckd Ldl Lipidmentioning
confidence: 99%
“…Compared with ageand gender-matched controls, there are increased levels of inflammatory markers in the coronary vessels and blood of CKD patients [28][29][30] . Multiple putative risk factors for coronary artery disease (CAD) are present in CKD patients, including insulin resistance, increased oxidative stress, inflammation, anemia, excessive smoking, endothelial dysfunction, and reduced nitric oxide availability 31,32) . When present, proteinuria and the consequent hypoalbuminemia contribute to altered lipid abnormalities in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the dialysis method used may alter lipid profile, for example, the type of dialyzer membrane (cellulose-triacetate or polysulfone) [7] and the type of dialyzer buffer (bicarbonate-based or acetate) [8] [9].…”
Section: Introductionmentioning
confidence: 99%